EFEKTIVITAS PENGGUNAAN MODUL PEMBELAJARAN BIOLOGI BERBASIS KONTEKSTUAL PADA POKOK BAHASAN EKOSISTEM SISWA KELAS X DI SMAN 1 RAMBATAN - Yerita, Heppy; Haviz, M.; Rahmi, Elvy (Jurnal Pembelajaran MIPA, 2014)
The purpose of this research is to see the effectivity of using module in Biology learning process contextual-based in âEcosystemâ for SMAN 1 Rambatan, class X. This is semu-experimental research and descriptive by Randomized Control Group Only Design. The procedure of this research divided into 3 steps; planning, actuating, and finishing. The research instrument is final test, observation paper, angket. The result of this research shows that there is the difference of mean, standar deviasi and variants between experiment-class and control-class. The study result of students that given module is better than students that taught by convensional system. So, we can conclude that the effectiveness of the module that used can be reached.Key Words : effectivity, module, contextual, ecosystem